Adolescents Exposed to Cumulative Natural Disasters: A Comparison Between their Realities in Rural and Urban Areas - Pouliot, Eve; Maltais, Danielle; Gervais, Christine; Tardif-Grenier, Kristel; Simard, Ann-Sophie; Gauthier, Pascal; Maltais-Dufour, Olivia; Hamel, Ariane (Prehospital and Disaster Medicine, 2023)
Introduction: Over the past years, the Outaouais region (Quebec, Canada) and their residents have had to endure no less than five natural disasters (floods, tornadoes). These disasters are likely to have a variety of consequences on the physical and mental health of adolescents, as well as on their personal, family, school and social lives. The experiences of teenagers are also likely to vary depending on whether they live in rural or urban areas. Method: Data were collected via a self-administered questionnaire in February 2022. A total of 1307 teenagers from two high schools participated in the study by completing an online survey. The questionnaire measured various aspects of the youth's mental health using validated tests, such as manifestations of post-traumatic stress, anxiety and depression, as well as the presence of suicidal thoughts and self-harm. Other aspects of the youth's experience were measured, including their level of social support, school engagement, alcohol and drug use, and coping strategies. Results: One third of young students (n=1307) were experiencing depressive symptoms and suicidal thoughts, as well as significant daily stress. More than 25% of the students had moderate or severe anxiety and thoughts of self-harm. These problems were significantly more prevalent among youths with prior exposure to a natural disaster. The study data also revealed that youths living in rural areas had a more worrying profile than those living in urban areas. Conclusion: Similar to other studies (Ran et al., 2015; Stratta et al., 2014), our research data revealed that youths living in rural areas presented a more concerning profile than those residing in urban areas. It therefore seems important, in future studies and services, to focus more specifically on these teenagers to better understand their needs and to develop adapted services more likely to meet them.

Intersectoral approaches: the key to mitigating psychosocial and health consequences of disasters and systemic risks - Gousse-Lessard, Anne-Sophie; Gachon, Philippe; Lessard, Lily; Vermeulen, Valérie; Boivin, Maxime; Maltais, Danielle; Landaverde, Elsa; Généreux, Mélissa; Motulsky, Bernard; Le Beller, Julien (Disaster Prevention and Management: An International Journal, 2023)
Purpose The current pandemic and ongoing climate risks highlight the limited capacity of various systems, including health and social ones, to respond to population-scale and long-term threats. Practices to reduce the impacts on the health and well-being of populations must evolve from a reactive mode to preventive, proactive and concerted actions beginning at individual and community levels. Experiences and lessons learned from the pandemic will help to better prevent and reduce the psychosocial impacts of floods, or other hydroclimatic risks, in a climate change context. Design/methodology/approach The present paper first describes the complexity and the challenges associated with climate change and systemic risks. It also presents some systemic frameworks of mental health determinants, and provides an overview of the different types of psychosocial impacts of disasters. Through various Quebec case studies and using lessons learned from past and recent flood-related events, recommendations are made on how to better integrate individual and community factors in disaster response. Findings Results highlight the fact that people who have been affected by the events are significantly more likely to have mental health problems than those not exposed to flooding. They further demonstrate the adverse and long-term effects of floods on psychological health, notably stemming from indirect stressors at the community and institutional levels. Different strategies are proposed from individual-centered to systemic approaches, in putting forward the advantages from intersectoral and multirisk researches and interventions. Originality/value The establishment of an intersectoral flood network, namely the InterSectoral Flood Network of Québec (RIISQ), is presented as an interesting avenue to foster interdisciplinary collaboration and a systemic view of flood risks. Intersectoral work is proving to be a major issue in the management of systemic risks, and should concern communities, health and mental health professionals, and the various levels of governance. As climate change is called upon to lead to more and more systemic risks, close collaboration between all the areas concerned with the management of the factors of vulnerability and exposure of populations will be necessary to respond effectively to damages and impacts (direct and indirect) linked to new meteorological and compound hazards. This means as well to better integrate the communication managers into the risk management team.
Keywords: Boivin_Maxime; Gachon_Philippe; Gousse-Lessard_Anne-Sophie; Généreux_Mélissa; Infolettre; Infolettre_Fevrier_2023; Lessard_Lily; Site_internet_RIISQ

Stressed and distressed: how is the COVID-19 pandemic associated with sexual frequency, sexual satisfaction, and relationship satisfaction? - Dion, Jacinthe; Hamel, Catherine; Prévost, Benjamin; Bergeron-Leclerc, Christiane; Pouliot, Eve; Maltais, Danielle; Grenier, Josée; Dubé, Myriam; Ouellet-Plamondon, Claudiane; Vaillancourt-Morel, Marie-Pier (The Journal of Sexual Medicine, 2023)
Abstract Background The Canadian government’s response to the ongoing COVID-19 pandemic included the implementation of several restrictive measures since March 2020. These actions sought to decrease social contact and increase physical distancing, including that within universities. Such constraints were required to impede the transmission of the virus; however, concerns remain about their impact on the sexual and intimate relationships of university employees and students. Aim This study examined the associations between COVID-19–related stress and sexual frequency, sexual satisfaction, and relationship satisfaction, also testing the mediating role of psychological distress. Methods The models were tested with Canadian data collected from university employees and students in 2 phases: the first wave in April-May 2020 (T1; n = 2754) and the second wave in November-December 2021 (T2; n = 1430), 18 months afterward. Participants completed self-report questionnaires online. Path analyses were performed to test the associations of the mediation models. Outcomes The principal outcomes included psychological distress determined via the Patient Health Questionnaire–4, relationship satisfaction measured via the Dyadic Adjustment Scale, and sexual satisfaction and sexual frequency ascertained through a single item each. Results Overall, COVID-19–related stress was associated with higher psychological distress, which in turn was related to lower sexual frequency, sexual satisfaction, and relationship satisfaction. Similar results were obtained with T1 and T2 data, indicating the mediating effect of psychological distress. Clinical Implications These findings increase scholarly comprehension of the negative associations between stress/distress and sexual and romantic relationships. Sexuality and close relationships are vital to the quality of human life; thus, targeted interventions should be developed to reduce COVID-19–related stress and its impact on sexual and romantic relationships to mitigate the long-term influences of this unique global challenge. Strengths and Limitations To our knowledge, this study is the first to use a large sample size and replicate findings in 2 waves. Nonetheless, it is limited by the use of cross-sectional data. Longitudinal studies with the same participants are mandated to better understand the evolution of these outcomes. Conclusion COVID-19–related stress and psychological distress were found among participating university students and employees and were associated with lower sexual satisfaction, sexual frequency, and intimate relationship satisfaction. These results were observed at the early onset of the pandemic and 18 months afterward, suggesting that the stress generated by the pandemic were not mere reactions to the onset of the pandemic but persisted over time.